Russian roulette with unlicensed fat-burner drug 2, 4-dinitrophenol (DNP): evidence from a multidisciplinary study of the internet, bodybuilding supplements and DNP users. Issue 1 (December 2015) - Petróczi, Andrea; Ocampo, Jorge; Shah, Iltaf; Jenkinson, Carl; New, Rachael; James, Ricky; Taylor, Glenn; Naughton, Declan
Abstract Background 2, 4-Dinitrophenol (DNP) poses serious health-risks to humans. The aims of this three-stage multidisciplinary project were, for the first time, to assess the risks to the general public from fraudulent sale of or adulteration/contamination with DNP; and to investigate motives, reasons and risk-management among DNP-user bodybuilders and avid exercisers. Methods Using multiple search-engines and guidance for Internet research, online retailers and bodybuilding forums/blogs were systematically explored for availability of DNP, advice offered on DNP use and user profiles. Ninety-eight pre-workout and weight-loss supplements were purchased and analysed for DNP using liquid-chromatography-mass-spectrometry. Psychosocial variables were captured in an international sample of 35 DNP users (26.06 ± 6.10 years, 94.3 % male) with an anonymous, semi-qualitative self-reported survey. Results Although an industrial chemical, evidence from the Internet showed that DNP is sold 'as is', in capsules or tablets to suit human consumption, and is used 'uncut'. Analytical results confirmed that DNP is not on the supplement market disguised under fictitious supplement names, but infrequently was present as contaminant in some supplements (14/98) at low concentration (<100mcg/kg). Users make conscious and 'informed' decisions about DNP; are well-prepared for the side-effects and show nonchalant attitude toward self-experimentation with DNP. Steps are often taken to ensure that DNP is genuine. Personal experience with performance- and appearance enhancing substances appears to be a gateway to DNP. Advice on DNP and experiences are shared online. The significant discrepancy between the normative perception and the actual visibility suggests that DNP use is-contrary to the Internet accounts-a highly concealed and lonesome activity in real life. Positive experiences with the expected weight-loss prevail over the negative experiences from side effects (all but two users considered using DNP again) and help with using DNP safely is considered preferable over scare-tactics. Conclusion Legislation banning DNP sale for human consumption protects the general public but DNP is sold 'as is' and used 'uncut' by determined users who are not dissuaded from experimenting with DNP based on health threats. Further research with stakeholders' active participation is imperative for targeted, proactive public health policies and harm-reduction measures for DNP, and other illicit supplements.